The factors associated with mental health and the impact of COVID-19 - Martinez, Linda; Perley, Rebecca; Alani, Salim; O’Lawrence, Henry (Journal of Community Medicine and Health Solutions, 2022)
The mental health impact caused by COVID-19 on adolescents was reviewed, and due to limited data, adult results were included, to support our assertion that additional mental health resources are needed for both adult and young people. Positive gains would include improved socio-emotional skills, a decrease in maladaptive behaviors contributing to the disruption in interpersonal relationships and lifetime achievements, suicide attempts and psychopathology, persistent mental health concerns found in the juvenile justice and foster care systems and substance use addiction later in adulthood (The American Psychological Association, 2019; Garber & Weersing, 2010; Office of Juvenile Justice and Delinquency Prevention, n.d.; Tomasello, 2018;). Geiger & Davis, 2019, found that 13% or 3.2 million United States (U.S.) teenagers aged 12 - 17 years old experienced at least one major depressive episode with the depression rate increasing 59% from 2007 to 2017. Therefore, we assert that developing programs to overcome barriers to mental health aid can reduce instances experienced in adolescence and adulthood.